2021
DOI: 10.3390/cancers13215381
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Tumor Site-Specific Survival of Bone Sarcomas from 1980 to 2018: A Surveillance, Epidemiology and End Results-Based Study

Abstract: Objectives: As diagnosis and treatment guidelines for bone sarcomas continue updating, it is important to examine whether, when, and which kinds of patients have had a survival improvement over the last four decades. Methods: This cohort study included 9178 patients with primary bone and joint sarcomas from 1 January 1980 to 31 December 2018 using data from Surveillance, Epidemiology and End Results (SEER)-9 Registries. The follow-up period was extended to November 2020. Patients were divided by decade into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
(44 reference statements)
0
18
0
1
Order By: Relevance
“…Since the 1970s, the development of cytotoxic chemotherapy has provided improvements in the prognoses of bone sarcoma patients, especially for those with osteosarcoma or Ewing sarcoma. After the 2000s, however, the prognoses of bone sarcoma patients have remained at a plateau, though many new targeted drugs and immunotherapies have been established for cancer therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, the development of cytotoxic chemotherapy has provided improvements in the prognoses of bone sarcoma patients, especially for those with osteosarcoma or Ewing sarcoma. After the 2000s, however, the prognoses of bone sarcoma patients have remained at a plateau, though many new targeted drugs and immunotherapies have been established for cancer therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pelvis is the most common anatomic site at which malignant bone tumors occur, whether primary or metastatic. It is reported that approximately 16.2% of primary bone sarcomas are located in the pelvis, e.g., pelvic chondrosarcoma, osteosarcoma, or Ewing tumor, causing a poor five-year survival rate of 45.0~57.5% [ 1 ]. The pelvic bone is also a common destination of many major metastatic cancers, such as lung and breast cancers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone sarcoma is a rare component of malignant solid tumors, which are divided into a variety of histological types, including osteosarcoma (OS), chondrosarcoma, Ewing sarcoma, and chordoma which are the most common types of bone malignancies [ 1 ]. Distinct histological sarcomas have different clinical characteristics and results [ 2 ]. OS is one of the most common bone malignancies, accounting for 20% and 40% of all bone cancers, and is highly heterogeneous in terms of histological type, tumor site, and age of onset [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distinct histological sarcomas have different clinical characteristics and results [ 2 ]. OS is one of the most common bone malignancies, accounting for 20% and 40% of all bone cancers, and is highly heterogeneous in terms of histological type, tumor site, and age of onset [ 2 , 3 ]. Patients with local OS can achieve a 5-year survival rate of more than 70% through surgery combined with neoadjuvant and postoperative chemotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%